Representing Interfaith Dialogue in Digital Media: A Study of Religious Representation on Daniel Mananta’s YouTube Channel - Habibah, Umi; Muhammad Afdillah (Journal of Islamic Philosophy and Contemporary Thought, 2024)
As a country with six officially recognized religions, Indonesia faces significant challenges in fostering interfaith harmony amidst its diversity. One factor influencing this dynamic is the role of social media, which can be used to promote religious tolerance and create spaces for interfaith dialogue. As a popular social media platform, YouTube has become an important medium for presenting interfaith dialogue content that encourages diversity awareness. One YouTube channel offering such content is Daniel Mananta’s channel, with his program “Daniel Tetangga Kamu” (Daniel, Your Neighbour), which features interfaith dialogue. This study aims to analyze how religion and interfaith dialogue are represented in the program, using Stuart Hall’s theory of representation. This study examines five video podcasts containing interfaith dialogue with guests from various religious backgrounds, selected based on the highest number of viewers during the 2021-2022 period. The results indicate that Daniel Mananta presents four typologies in depicting religion: inclusivism, pluralism, eclecticism, and universalism, reflecting a tolerant attitude toward religious differences within Indonesian society.